Inovasi Media Sosial dan Pengaruhnya terhadap Penerapan Fotografi Fashion - Irdha Yunianto; Wiwid Wahyudi; Agus Priyadi (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The development of information technology brings a change in society. The birth of social media caused people's behavior patterns to experience a shift in existing culture, ethics and norms. The use of social media, especially Instagram, is currently the focus used in providing information. Almost all levels of society use social media to communicate. There are many new ideas that can be used to utilize social media, one of which is as a promotional medium in the field of fashion photography. The increasingly developing fashion industry must of course also be balanced with fashion photography. Therefore, one of the industries in the field of photography, namely Photoin Studio, continues to innovate using social media to play an important role in influencing society. By using a qualitative approach and semiotic analysis from Charles Sanders Peirce, you can find out and understand this research.